EVALUASI LINGKUNGAN UNTUK FONDASI DI DAERAH LAPUKAN BREKSI VULKANIK, JATINANGOR, SUMEDANG, JAWA BARAT - -, Zufialdi Zakaria (Fakultas Teknik Geologi Universitas Padjadjaran, 2006)
Jatinangor consist of volcanic brecia and its weathered. This terrain as development area. This terrain is require some analysis to it land development, for example is foundation analysis. To anticipate of negative impact as effect of foundation failure, hence requireded by calculation of bearing capacity. Also required environmental analysis by Environmental Evaluation by identifying impact and also give environmental management instruction and also environmental monitoring that started with location of foundation at appropriate deepness. Monitoring herein can be done to condition of building (house, bridge, drainage, road, street, etc.).